Effect of different organic supplements and casing mixtures on yield of two strains of milky mushroom (Calocybe indica) - PRASHANT MISHRA; RAMJI SINGH, RAVINDER KUMAR*, GOPAL SINGH, (Indian Phytopathology, 2012)
The present study was designed to assess the effects of eleven organic supplements as substrate and casing as well as casing mixtures on yield of two strains (CI-6&CI-4) of milky mushroom. Minimum time 17.3 and 17.7 days was recorded for spawn run in the mustard cake supplemented substrate as well as 9.7 and 10.0 days for pinhead formation, 17.3 and 18.0 days for first harvesting from strains CI-6 and CI-4, respectively. Maximum yield was obtained from soybean flour supplemented substrate 648.3 and 599.7 g/kg of dry substrate as well as in same supplemented casing least days showed for pinhead formation 11.3 and 10.3 days and maximum number of pinhead initiation 71.0 and 70.7/bag, whereas maximum yield 616.0 and 588.3g/kg of dry substrate was harvested in neem cake supplemented casing from strains CI-6 and CI-4, respectively. The combination of casing mixture FYM+VC+PM (1:1:1) took less period for pinhead formation 12.0 and 12.3 days and 20.0 and 20.7 days for first harvesting, while maximum yield 607.0 and 591.7g/kg of dry substrate was harvested with casing mixture FYM+VC+GS (1:1:1) from strain CI-6 and CI- 4, respectively. Among the tested casing thickness, the 0.5 cm/200 gm took less period 9.3 and 11.0 days for pinhead formation and 18.3 and 17.3 days for first harvesting, while maximum yield 559.0 and 544.7g/kg of dry substrate was recorded in casing thickness 2.5 cm/1000gm from strains CI-6 and CI-4, respectively.